The social network of alcohol users undergoing treatment in a mental health service Red social de adictos al alcohol bajo tratamiento en un servicio de salud mental Rede social de usuários de álcool, sob tratamento, em um serviço de saúde mental - Jacqueline de Souza; Luciane Prado Kantorski; Gabriela Pereira Vasters; Margarita Antonia Villar Luis (Universidade de São Paulo, 2011)
The treatment of alcohol and drug users requires an extended reflection on the influence of the family and other social network groups of these individuals. Thus, this study, results of a qualitative study, aimed at investigating the presence of drug users in the social network of individuals undergoing treatment and the possible interventions of the mental health services in the social network of four users of alcohol in the municipality of Alegrete/RS. Interviews with users and families, genograms and eco-maps were used. The results indicated the presence of drug users in the family and in the other social network groups, and that the group for chemical dependants was the main intervention in these social networks. These results demonstrate the need for directing the actions of mental health to develop healthy bonds, to expand the social network and structure of the group in order to provide benefits which favor effective psychosocial rehabilitation. El tratamiento de adictos al alcohol y drogas requiere una reflexión amplia sobre la influencia de la familia y otros grupos de la red social de estos individuos. Así, este estudio, resultado de una investigación cualitativa, objetivó averiguar la presencia de usuarios de drogas en la red social de individuos bajo tratamiento y las posibles intervenciones del servicio de salud mental en la red social de cuatro adictos al alcohol en el municipio de Alegrete/ RS. Fueron utilizadas entrevistas con adictos y familiares, genograma y ecomapa. Los resultados indicaron la presencia de adictos de drogas en la familia y demás grupos de las redes sociales y el grupo para dependientes químicos como principal intervención en estas redes sociales. Estos resultados evidencian la necesidad de dirigir las acciones de salud mental para el desarrollo de vínculos saludables, ampliación de la red social y estructuración del grupo de modo a proporcionar beneficios en pro de una efectiva rehabilitación psicosocial. O tratamento de usuários de álcool e drogas requer reflexão ampliada sobre a influência da família e outros grupos da rede social desses indivíduos. Assim, este estudo, resultado de pesquisa qualitativa, objetivou averiguar a presença de usuários de drogas na rede social de indivíduos sob tratamento e as possíveis intervenções do serviço de saúde mental, na rede social de quatro usuários de álcool, no município de Alegrete, RS. Foram utilizadas entrevistas com usuários e familiares, genograma e ecomapa. Os resultados indicaram a presença de usuários de drogas na família e demais grupos das redes sociais e o grupo para dependentes químicos como principal intervenção nessas redes sociais. Os resultados evidenciam a necessidade de direcionamento das ações de saúde mental para o desenvolvimento de vínculos saudáveis, ampliação da rede social e estruturação do grupo, de modo a proporcionar benefícios em prol de efetiva reabilitação psicossocial.